Effect of reentrant cone geometry on energy transport in intense laser-plasma interactions - Lancaster, K; Sherlock, M; Green, J; Gregory, C; Hakel, P; Akli, K; Beg, F; Chen, SN; Freeman, R; Habara, H; Heathcote, R; Hey, D; et al. (2009)
The energy transport in cone-guided low- Z targets has been studied for laser intensities on target of 2.5× 1020 W cm-2. Extreme ultraviolet (XUV) imaging and transverse optical shadowgraphy of the rear surfaces of slab and cone-slab targets show that the cone geometry strongly influences the observed transport patterns. The XUV intensity showed an average spot size of 65±10 μm for slab targets. The cone slabs showed a reduced spot size of 44±10 μm. The shadowgraphy for the aforementioned shots demonstrate the same behavior. The transverse size of the expansion pattern was 357±32 μm for the slabs and reduced to 210±30 μm. A transport model was constructed which showed that the change in transport pattern is due to suppression of refluxing electrons in the material surrounding the cone. © 2009 The American Physical Society.